Social Communication in Big Brown Bats - Montoya, Jessica; Lee, Yelim; Salles, Angeles (Frontiers in Ecology and Evolution, 2022)
Bats are social mammals that display a wide array of social communication calls. Among them, it is common for most bats species to emit distress, agonistic, appeasement and infant isolation calls. Big brown bats (Eptesicus fuscus) are no different: They are gregarious animals living in colonies that can comprise hundreds of individuals. These bats live in North America and, typically found roosting in man-made structures like barns and attics, are considered common. They are insectivorous laryngeal echolocators, and while their calls and associated brain mechanisms in echolocation are well documented, much less is known about their neural systems for analyzing social vocalizations. In this work we review what we know about the social lives of big brown bats and propose how to consolidate the nomenclature used to describe their social vocalizations. Furthermore, we discuss the next steps in the characterization of the social structure of this species and how these studies will advance both research in neuroethology and ecology of big brown bats.